Figure out the translation components, and then where point P' ends up:

Translation: (
,)
Let P = (-4, -3).
P' = (
,)

2.

Figure out the translation components, and then where point P' ends up:

Translation: (
,)
Let P = (-4, -1).
P' = (
,)

1.

The transformation ABCD → A'B'C'D' is a rotation around (3, 2) by °
Rotate P around (3, 2) by the same angle. (You may need to sketch things out on paper.) P' = (
,)

2.

The transformation ABCD → A'B'C'D' is a rotation around (1, 3) by °
Rotate P around (1, 3) by the same angle. (You may need to sketch things out on paper.) P' = (
,)

1.

Transformation ABCD → A'B'C'D' is a reflection across the line
e.g. y=-3, y=x.
Reflect P over the same line. (You may need to sketch things out on paper.)
P' = (
,)

2.

Transformation ABCD → A'B'C'D' is a reflection across the line
e.g. y=-3, y=x.
Reflect P over the same line. (You may need to sketch things out on paper.)
P' = (
,)